Peningkatan Efisiensi Pemerintahan Desa melalui Pemberdayaan Struktur Organisasi dengan Metode Knowledge Sharing dan Innovation Capability - Dwi Putri Yuliani; Angelina Elizabet Hutasoit (Jurnal Perlindungan Masyarakat: Bestuur Praesidium, 2024)
The importance of village organizational structures in the context of knowledge sharing and innovation is key to increasing the capacity and effectiveness of village government. This article explains that the village organizational structure has a significant impact on the pattern, direction, attitude and coordination in sharing knowledge between elements of the village organization. By exploiting opportunities in the dimensions of complexity, formalization and centralization, organizational structure empowerment can be carried out to achieve village development goals. Village leaders have an important role in increasing capacity and adaptability to changing times. An effective knowledge sharing process in village government can encourage innovation, increase performance effectiveness, and approach the goals desired by the community. The importance of having an open mindset and an environment that supports free expression is also emphasized as the main key in creating innovation. Through literature analysis, this article concludes that village organizational structure influences the pattern and direction of knowledge sharing, which ultimately influences the capacity and effectiveness of village government. To achieve this, empowering organizational structures need to focus on the dimensions of complexity, formalization and centralization. By reducing complexity and increasing formalization, the process of knowledge sharing and innovation can be facilitated, supporting the achievement of village development goals.